2011
DOI: 10.1016/j.neuroscience.2011.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels and ionotropic receptors in human embryonic stem cell derived neural progenitors

Abstract: Human neural progenitor cells differentiated from human embryonic stem cells offer a potential cell source for studying neurodegenerative diseases and for drug screening assays. Previously, we demonstrated that human neural progenitors could be maintained in a proliferative state with the addition of leukemia inhibitory factor and basic fibroblast growth factor. Here we demonstrate that 96 hours after removal of basic fibroblast growth factor the neural progenitor cell culture was significantly altered and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 57 publications
(73 reference statements)
2
46
0
Order By: Relevance
“…4) imply that a greater number of cells reach a more advanced differentiated stage and express neuronal markers, even though an equal percentage exited the progenitor state. Given that these NP cells do not differentiate to glial cells under the conditions used in this study [70], present results implied a positive role of LIF for increasing the yield of pan-neuronal cells during in vitro differentiation.…”
Section: Lif Increased Proliferation Stat3 Signaling and Yield Of Dmentioning
confidence: 62%
See 1 more Smart Citation
“…4) imply that a greater number of cells reach a more advanced differentiated stage and express neuronal markers, even though an equal percentage exited the progenitor state. Given that these NP cells do not differentiate to glial cells under the conditions used in this study [70], present results implied a positive role of LIF for increasing the yield of pan-neuronal cells during in vitro differentiation.…”
Section: Lif Increased Proliferation Stat3 Signaling and Yield Of Dmentioning
confidence: 62%
“…This implies that a certain proportion of cells counted as NP cells could be early neurons. HuC/D is a RNA binding protein expressed in the cell bodies of early postmitotic neurons [66][67][68][69][70][71][72][73][74][75][76][77][78], and MAP2 marks dendrites of differentiated neurons [69] (Fig. 4).…”
Section: Lif Increased Proliferation Stat3 Signaling and Yield Of Dmentioning
confidence: 99%
“…In neural progenitors derived from hESCs after 30 days in culture, Malmersjo et al observed an increase in [Ca 2 + ] i evoked by 50 mM K + , but they did not specify which type of VOCC was activated [22]. Using reverse transcript (RT)-polymerase chain reaction (PCR) studies, others have shown the upregulation of VOCC expression in differentiated hESCs [23]. L-type channels are also expressed in NPs derived from human [25] and mouse ESCs [24].…”
Section: Expression Of Vocc In P7 Hesc Npsmentioning
confidence: 99%
“…To the best of our knowledge there is only 1 study by Young et al [23] that has demonstrated the presence of purinergic receptors in hESC-derived neural progenitors. Though the authors did not perform functional studies on P2 receptors, they showed by RT-PCR that in the hESC line WA09, the P2X 4 subunits are upregulated in hNPs but downregulated in differentiated hNPs, while P2X 7 was not expressed at any stage.…”
Section: Purinergic Receptor Activation In P7 Hesc Npsmentioning
confidence: 99%
See 1 more Smart Citation